Quantitative assessment of Bell's palsy-related facial thermal asymmetry using infrared thermography: A preliminary study - Liu, Xulong; Feng, Jinghui; Zhang, Ruohui; Luan, Jingmin; Wu, Zhenying (Journal of thermal biology, 2021)
The temperature distribution of normal human skin is symmetrical. Facial paralysis generally changes this thermal symmetry. The aim of this study is to analyze facial thermal asymmetry during the early onset of Bell's palsy, and to assess the feasibility of the diagnosis of early-onset Bell's palsy using infrared thermography (IRT). Fifteen subjects with Bell's palsy and 15 healthy volunteers were considered in this study. The infrared thermal images of the front, left, and right sides of all the subjects were collected and analyzed. Each group of facial thermograms was divided into 16 symmetrical regions of interest (ROIs) with respect to the left and right sides. Three different temperature difference calculation methods were used to express the degree of thermal symmetry between the left- and right-side ROIs, namely, the mean temperature difference (ΔTroi), maximum temperature difference (ΔTmax), and minimum temperature difference (ΔTmin). Among the facial ROIs, there were significant differences in the thermal symmetries of the frontal region, medial canthus region, and infraorbital region between subjects with and without Bell's palsy (p < 0.05). Based on the results, ΔTroi was more effective than the other two methods for the diagnosis of early-onset Bell's palsy. The area under the ROC curve (AUC) of ΔTroi in the infraorbital region was 0.818; and the sensitivity and specificity were 0.867 and 0.800, respectively. Subjects with early-onset Bell's palsy exhibited thermal asymmetry on the left and right sides of their faces. The diagnosis of early-onset Bell's palsy using IRT is therefore necessary. Nevertheless, more effective thermal symmetry analysis methods will be investigated further in future research. •Facial thermal asymmetry due to Bell's palsy was evaluated by infrared thermography.•Differences in facial thermal distributions of subjects with/without Bell's palsy.•Facial thermal asymmetry is not consistent with the symptoms of Bell's palsy.•Frontal-face thermal imaging is helpful for the early diagnosis of Bell's palsy.